Response Mechanisms and New Approaches with Solid-State Ion-Selective Electrodes: A Powerful Multitechnique Materials Characterization Approach - De Marco, Roland; Jiang, Zhong-Tao; Becker, Thomas; Clarke, Graeme; Murgatroyd, G.; Prince, K. (Wiley-VCH Verlag GmbH, 2006)
In modern materials science, there is a plethora of characterization techniques of materials that can provide valuable insights into the fundamental chemical physics of solid-state devices such as chalcogenide glass ion-selective electrodes (ISEs). In this paper, electrochemical impedance spectroscopy (EIS), X-ray photoelectron spectrometry (XPS) and secondary ion mass spectrometry (SIMS) have been used in the elucidation of the mechanistic chemistry of the cadmium chalcogenide glass ISE. Furthermore, in situ synchrotron radiation-grazing incidence X-ray diffraction (SR-GIXRD), in situ EIS/SR-GIXRD, along with small angle neutron scattering (SANS), can be used to unravel the complex relationship between the nanostructure, bulk electrical conductivity and concomitant electrochemical reactivity of an iron chalcogenide glass ISE. Significantly, exciting preliminary modified atomic force microscopy (AFM) data utilizing AFM cantilevers with attached microparticles of the copper sensing material jalpaite demonstrate the tremendous potential of selective force ISE-AFM in the imaging of important molecular structures such as the copper ion channels of cell membranes in fish gills and/or phytoplankton